Self Efficacy Matematika Melalui Problem Based Instruction (PBI) Dalam Pendekatan Aptitude Treatment Interaction (ATI): Studi Eksperimen di SMP Negeri 1 Kuindra - Aris Eko Suhendra; Risnawati (Milenial: Journal for Teachers and Learning, 2021)
The objective of this research was to tried the above effect towards mathematic self-efficacy of students taught using Problem Based on Instruction model on Aptitude Treatment Interaction with the students taught using Aptitude Treatment Interaction approach. The formulation of this research was whether problem based on instruction influenced towards self-efficacy of students and how it’s effect to it?. This research was designed as Intact-Group Comparison which was part of Pre-Experimental Designs where one group was divided into two groups; both were experiment group and control group. The writer in this research took role in the process of teaching. The subject of t this research was eight year students at state junior high school 1 KUINDRA district of Indragiri Hilir. While the object was self-efficacy of students. The data in this research was collected using documentation, observation test and questionnaires. The meetings in this research was conducted six times, five times of them were conducted using PBI model on ATI Approach and one another meeting by filing up the questionnaires and measured using likert scale and by using test-t and the effect on problem based on instruction calculated using Kp. Based on data analysis, the writer concluded that the effect of PBI model on ATI approach influenced towards students’s high ability it was around 41,44%, students’s ability of middle was 40,55% and student’s ability of low was 37,27%.